The “golden age” of Russian serfdom - O. Yu. Yakhshiyan (Вестник университета, 2022)
The article attempts to show the apogee of Russian serfdom as one of the most significant direct and immediate results of Peter the Great’s transformations. The proprietary (proprietorial) interest of the landed gentry in relation to the local lands and peasants received a previously unthinkable impulse due to Peter’s elevation of the status of estates to patrimonial, as well as the erasure of the legal boundary between serfs and peasants by turning both into “audit souls” during the tax reform. Already in the last years of Peter the Great’s reign, the authorities were inclined to identify the right of landlords to peasants with the right to immovable property in the context of the evolution of serfdom in Russia. The article discusses in detail the practice of distribution by emperors and empresses of lands with peasants into ownership as a reward for special merits. The author analyzed the post-Petrine legislation that expanded the class privileges of the nobility and strengthened their ownership rights in relation to landlords and peasants. Particular attention is paid to the practice of selling landlord peasants without land and with the separation of families. The historical significance of Peter’s and post-Peter’s policies of a sharp strengthening of the ownership (proprietary) rights of nobles to land and peasants in their estates lies primarily in the accumulation of a powerful conflict potential in Russian society for the long term. The “time bomb” laid by Peter I and his immediate successors in the inter-verbal relations of the local nobility and the peasantry dependent on it will explode at the beginning of the twentieth century, and it will give rise to a great peasant revolution in Russia.